1992
DOI: 10.1007/bf00386933
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in silicosis

Abstract: In order to assess the effect of silicosis on lung function, 61 gold miners with radiological silicosis were compared with 61 controls. Each pair was matched for age, dust exposure, and smoking habits. A full range of lung function tests was performed, and with two exceptions the results showed no significant differences between the two groups. The exceptions are the slope of the alveolar plateau (phase 3) and the closing volume, for which the silicotic cases had significantly higher values. The reason for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Silicosis is a chronic diffuse interstitial lung disease, caused by long term inhalation of quartz dust. Lung function loss is described in several forms of pneumoconiosis (nodular silicosis [Cowie and Mabena, 1991], mixed dust fibrosis [Begin et al, 1988;Ng and Chan, 1992;Wiles et al, 1992;Wang et al, 1997], and Coal Workers Pneumoconiosis [Wang et al, 1999]) caused by exposure to quartz containing dust, but not consistently. It is recognized, however, that associations between pneumoconiosis and loss of lung function can be obscured as a result of selection bias [Eisen et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Silicosis is a chronic diffuse interstitial lung disease, caused by long term inhalation of quartz dust. Lung function loss is described in several forms of pneumoconiosis (nodular silicosis [Cowie and Mabena, 1991], mixed dust fibrosis [Begin et al, 1988;Ng and Chan, 1992;Wiles et al, 1992;Wang et al, 1997], and Coal Workers Pneumoconiosis [Wang et al, 1999]) caused by exposure to quartz containing dust, but not consistently. It is recognized, however, that associations between pneumoconiosis and loss of lung function can be obscured as a result of selection bias [Eisen et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…(26,29,30) Published studies suggest that pulmonary impairment, which may be greater among dust-exposed workers who also smoke, is associated with both cigarette smoking and cumulative dust exposure, irrespective of the presence or absence of abnormalities detected on a chest x-ray. (26,30,31,32) Pulmonary function testing revealed that eight (24%) of the 33 participants had abnormal spirometry patterns.…”
Section: Discussionmentioning
confidence: 99%
“…(31,32,33) A NIOSH evaluation at this same plant in 1979 found that 7 (27%) of 26 participating current and former workers with one or more years exposure had chest x-ray changes consistent with silicosis. (34) Three cases were identified among 15 current workers and four cases were identified among 11 former workers.…”
Section: Discussionmentioning
confidence: 99%